Relationship between decreased swimming velocity and muscle activity during 200-m front crawl - Ikuta, Y.; Matsuda, Y.; Yamada, Y.; Kida, N.; Oda, S.; Moritani, T. (European Journal of Applied Physiology, 2012)
The aims of this study were (1) to evaluate changes in muscle activity associated with physiological fatigue and decreased swimming velocity (SV) during 200 m of front crawl swimming, and (2) to examine the relationship between the decreased SV and changes in kinematic or electromyogram parameters. Twenty swimmers participated in a 4 × 50-m swim test. The surface EMG of 11 muscles (7 in the upper limbs and 4 in the lower limbs) was measured and the mean amplitude value (MAV) for one stroke cycle was obtained. The SV and arm angular velocity (AAV) of shoulder flexion during the first (early stroke) and second (late stroke) half of the underwater arm stroke were analyzed using an underwater camera. The AAV, the MAV of flexor carpi ulnaris (FCU), biceps brachii (BB), and triceps brachii during the early stroke, and the MAV of rectus femoris decreased along with a decrease in SV. In contrast, the MAV of the pectoralis major (PM) increased significantly in the final 50 m. The rate of change in MAVs (deltaMAVs) of FCU, BB and latissimus dorsi during the early stroke, and deltaMAV of biceps femoris were significantly correlated with deltaSV and/or deltaAAV. Positive correlations were identified between dMAVs of several muscles. However, no negative correlations were observed between deltaMAVs. These results suggest that the decrease in SV was related to decreases in the activities of several muscles that coordinated with each other, and that a compensating strategy occurred between PM and other muscles in the final 50 m.